Chapter 6: Climate Impacts on Agricultural Production, Food Supply and Food Availability in Five Livelihood Zones of Pakistan - Savelli, Adam; Schiek, Benjamin; Ghosh, Aniruddha; Achicanoy Estrella, Harold Armando; Esquivel, Alejandra; Saavedra, Cesar; Ramírez Villegas, Julián Armando; Grosjean, Godefroy; Abbas, Iftikhar; Maqbool, Shama; Jadoon, Arshad; Bidault, Nicolas; et al. (Sustainable Development Policy Instuitute, 2023)
In Pakistan, the impacts of climate change can lead to environmental conditions that will be extremely challenging for many forms of agricultural production critical to food security. This chapter summarises the results of a larger study that employs mixed methods research to project how climate change will impact agricultural production, food supply, and food availability across five livelihood zones by 2050. The modelled simulations predict increasing temperatures, and precipitation rainfall variability by 2050, resulting in increased drought conditions, flooding, and heat stress. These harmful trends will prevent the agricultural sector from reaching its full potential, likely causing food insecurity to become entrenched in agriculturally dependent areas where market access is limited and climate change limits the ability of vulnerable households to grow food for subsistence and income generation. To safeguard food security, provincial and sub-provincial governments should be supported in implementing national climate change policies at the local level; Pakistan’s social protection schemes should be expanded to cover climate vulnerable beneficiaries; anticipatory action must be prioritised to support communities before a hazard occurs; participatory interventions and the development of community assets are needed to safeguard agricultural livelihoods; and sustainable finance is required to facilitate long-term adaptation initiatives.